2017
DOI: 10.5301/ijbm.5000277
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Prognostic Role of Ki-67 Labeling Index in Gastric Carcinoma

Abstract: Background This meta-analysis aimed to elucidate the prognostic role of the Ki-67 labeling index (LI) in gastric cancer (GC). Methods The current study included 3,615 GC patients in 20 eligible studies, and evaluated the prognostic role of Ki-67 LI in GC. Subgroup analysis was conducted based on depth of invasion and cutoff value for high Ki-67 LI. Results A high Ki-67 LI correlated significantly with worse survival (hazard ratio [HR] = 1.214, 95% confidence interval [CI], 1.004-1.468). However, there was no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
3
0
2
Order By: Relevance
“…Although high Ki-67 expression was observed in 75% of patients with positive lymph node metastasis, the present study showed no statistically significant association between Ki-67 expression and lymph node metastasis (P = 1.00). This was in accordance with Pyo and Kim, (22) who reported similar results.…”
Section: Discussionsupporting
confidence: 93%
“…Although high Ki-67 expression was observed in 75% of patients with positive lymph node metastasis, the present study showed no statistically significant association between Ki-67 expression and lymph node metastasis (P = 1.00). This was in accordance with Pyo and Kim, (22) who reported similar results.…”
Section: Discussionsupporting
confidence: 93%
“…Our study suggested the cutoff of Ki-67 LI as 25% for DFS. A recent meta-analysis study by Pyo and Kim [26] also shows that Ki-67 LI ≤25% was correlated with worse survival in gastric cancer. However, the optimal cutoff value is still unclear in this field.…”
Section: Discussionmentioning
confidence: 98%
“…These factors are important because they are associated with a variety of critical clinical measures such as malignant potential and therapeutic strategies. Ki-67 quantification, performed using immunohistochemical (IHC) staining, is used as a proliferative marker [16]; however, immunohistochemistry (IHC) is expensive and has limited availability in resource-constrained regions. Quantification of proliferative activity by mitotic figures also plays a vital role in predicting tumor proliferation and is often quantitated via hematoxylin and eosin (HE) staining.…”
Section: Introductionmentioning
confidence: 99%